Voltage instability analysis for electrical power system using voltage stabilty margin and modal analysis - Mohamad Nor, Ahmad Fateh; Sulaiman, Marizan; Abdul Kadir, Aida Fazliana; Omar, Rosli (Institute of Advanced Engineering and Science (IAES), 2016)
Voltage instability analysis in electric power system is one of the most important factors in order to maintain the equilibrium of the power system. A power system is said to be unstable if the system is not able to maintain the voltage at all buses in the system remain unchanged after the system is being subjected to a disturbance.The research work presented in this paper is about the analysis of voltage instability of electric power system by using voltage stability margin (VSM), load real power (P) margin, reactive power (Q) margin, reactive power-voltage (QV) and real power-voltage (PV) modal analysis. IEEE 30-bus system has been chosen as the power system. The load flow analysis are simulated by using Power World Simulator software version 16. Both QV and PV modal analysis were done by using MATLAB application software.